2020
DOI: 10.1038/s41430-020-00760-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally sensitive agriculture—an approach to reducing hidden hunger

Abstract: Cereal-based diets of the people in developing countries are qualitatively deficient in micronutrients-vitamins and minerals-due to low intake of vegetables, fruits, legumes and foods of animal origin. Consumption of nutritious millets has also come down in India. Calorie sufficiency may ensure protein sufficiency (though not protein quality), but it does not ensure adequacy of micronutrients. Studies in several countries in Asia, and India show that with education and advocacy even farmers with small and marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Malnutrition can be in many forms, including hunger, obesity, and micronutrient deficiency [60]. Our results are similar to many other studies [4,32,33,61] and showed that cereal-based nutrition is common among WRA. A woman's diet in our sample was mainly based on noodles, bread, rice, buckwheat, potatoes, and other starchy foods.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Malnutrition can be in many forms, including hunger, obesity, and micronutrient deficiency [60]. Our results are similar to many other studies [4,32,33,61] and showed that cereal-based nutrition is common among WRA. A woman's diet in our sample was mainly based on noodles, bread, rice, buckwheat, potatoes, and other starchy foods.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies also show that women's education does not influence their diet quality [10]. Improving knowledge on proper nutrition should be performed [61]. Strategies for food preservation and its later consumption were common among households 30 years ago.…”
Section: Socio-economic Factors and Nutrition Adequacymentioning
confidence: 99%
See 1 more Smart Citation
“…A strong positive relationship between farm diversity and dietary diversity was also established by Jones et al [ 43 ]. There is also published literature on specific interventions such as positive impact of home garden interventions on intermediate nutritional incomes such as dietary diversity and consumption of nutrient rich foods [ 44 – 47 ]; improved consumption of animal source foods through integration of fishery [ 48 ], and livestock [ 44 , 49 ] and combination of nutrition garden and poultry together with nutrition awareness, improving consumption of vegetables and eggs [ 50 ]. However, this study is perhaps one of the first in designing a system-wide farming intervention (including field crops, vegetables and fruits, and animal source foods) based on resource availability, accompanied by nutrition awareness, to enhance dietary diversity of households primarily involved in agriculture and allied activities.…”
Section: Discussionmentioning
confidence: 99%
“…health issues associated with deficiencies in elements such as zinc, iron, iodine, selenium, or copper (Bamji et al 2020). These elements are often referred to as micronutrients or trace elements, as they are required only in tiny amounts in the alimentation, while being toxic at high doses.…”
mentioning
confidence: 99%